Pengaruh Media Sosial Terhadap Brand Awareness Pada Produk Asuransi Takaful Keluarga - Tambunan, M Azhari (CV. ITTC INDONESIA, 2023)
From the point of view of the insurance business is a company whose main business is receiving/selling services, transferring risks from other parties, and obtaining profits with various risks among a number of its customers. Sharia life insurance is risk management based on sharia principles to help and protect each other by providing payments based on the death or life of the participant, or other payments to participants or other parties who are entitled at a certain time as stipulated in the agreement, the amount of which has been determined and is based on results of fund management. Social media is an online platform that allows users to make social connections and communicate, collaborate, share and express themselves virtually. Social media has changed the way corporate tools and consumer communication strategies are used, especially in the marketing sector. Social media marketing focuses on business efforts to provide content that engages consumers, encourages them to engage with brands on social media platforms, and inspires them to share information. One of the most important elements of social media, according to marketers, is creating and maintaining feedback. This is so that through monitoring and feedback, marketers can learn to influence important social dialogue. Social media offers a variety of educational programs, visual exercises, blog articles and other activities that generate comments, allowing marketers to measure and understand user reactions to any content shared on social media. One of the factors that can affect a company's brand awareness is the media. Through media, customers can communicate in two ways with each other as well as with businesses and share text, images, audio, and video materials.